L’action publique urbaine des petites villes au défi de l’altermétropolisation - Élodie Texier (Bulletin de l’Association de Géographes Français)
This article aims at questioning the renewal of urban public action in small towns through the prism of altermetropolization. Since successive social and health crises, small towns in France have experienced unprecedented interest, both from geographical research and from public authorities. The “Small Towns of Tomorrow” action program launched at the end of 2020 seems to respond to this new impetus. While this could have encouraged public decision-makers to rethink the urban renovation of small towns and their city centers, it is clear that the neoliberal urban model remains dominant in the urban fabric. Then, we wondered if this “CAME” framework (Competitiveness, Attractiveness, Metropolization and Excellence) was also applied to the renovation of the city centers of small towns and if it responded to user expectations. To do this, we will rely on the results of a study carried out between 2020 and 2021 among users of four small towns (with a municipal population between 2,500 and 10,000 inhabitants) located in New Aquitaine region. By highlighting the gaps between local urban public action and the “expression” of users, these results will question the interest of user participation in the altermetropolisation process, by presenting a renewed hierarchy of functions urban centers of small towns.